Exhaustion of domestic remedies as a condition of lodging a complaint before the European Court of Human Rights - T. Gerasimenko (Правоприменение, 2017)
The subject. The article is devoted to the subject of the exhaustion of domestic remediesbefore filing a complaint to the European Court of Human Rights.The purpose. The purpose of this article is to show and reveal the characteristics of suchimportant condition of lodging a complaint before the European Court of Human Rights asthe exhaustion of domestic remedies.The methodology. The following scientific methods have been used to write this article:analysis, comparing and making conclusions.Results, scope of application. The right of individual petition is rightly considered to be thehallmark and the greatest achievement of the European Convention on Human Rights. Individualswho consider that their human rights have been violated have the possibility oflodging a complaint before the European Court of Human Rights. However, there are importantadmissibility requirements set out in the Convention that must be satisfied beforea case be examined. Applicants are expected to have exhausted their domestic remediesand have brought their complaints within a period of six months from the date of the finaldomestic decision. The obligation to exhaust domestic remedies forms part of customaryinternational law, recognized as such in the case – law of the International Court of Justice.The rationale for the exhaustion rule is to give the national authorities, primarily the courts,the opportunity to prevent or put right the alleged violation of the Convention. The domesticlegal order should provide an effective remedy for violations of Convention rights.Conclusions. The rule of exhaustion of domestic remedies is an important part of the functioningof the protection system under the Convention and its basic principle.